Penggunaan Pewarna Sintetis Dan Alam Pada Lukis Kain - Ariyana Damayanti; Yasinta Dwi Yulinda Sari (Garina, 2020)
Coloring materials for fabric painting can be produced from natural dyes and synthetic dyes. Natural and synthetic dyes have their respective advantages and disadvantages. The combination of the two colors will give the impression of a brighter color, and slightly reduce environmental pollution. The objectives of this research are: 1) Knowing the processing of synthetic and natural dyes for fabric painting; 2) Knowing the results of applying synthetic and natural dyes to fabric painting. The method used in this research is the research and development approach model Research and Development (R&D) and data analysis. Trials in this study were carried out with dye using 4 types of cloth with the help of a validator as an assessor of the coloring results. The results of this study indicate that synthetic dyes are lighter than natural dyes. Meanwhile, the colors produced from natural dyes tend to be darker. In painting this cloth, the writer needs a combination of dark and light colors. Therefore, the use of synthetic and natural dyes requires mixing of colors. The fading test conducted by the author for the color absorption of diamond crape on the fabric is very good. Thus it can be concluded that the use of natural and synthetic dyes can be applied to fabric painting by conducting trials first to get the right color.